Monitoring effects of lockdown during COVID-19 pandemic towards the air pollution in Southeast Asia / Nurul Fathimah Shamshudin and Nurul Rabitah Daud - Shamshudin, Fathimah; Daud, Nurul Rabitah (2022)
This research explores one of the most serious environmental threats to human health which is air pollution. The objective of this study is to examine the concentration of several air pollutants that has been affecting the atmosphere specifically in Southeast Asia after the emergence of the pandemic. Throughout this research, the air pollution concentration is monitored using several observation satellites such as NASA GIOVANNI, Ozone Monitoring Instrument (OMI), and MODIS-Aqua to see the difference in air quality before and after the lockdown was implemented in the selected specific area. The average mean for the studied year of each selected pollutant was also observed to see the pattern of the air quality after the pandemic. Thailand and other northern Southeast Asian nations bordering China were found to be the most affected by transboundary pollution, which was brought on by the climatological changes that all Southeast Asian countries experienced. In addition, most Southeast Asian nations are regarded as developing countries that rely significantly on power produced by fossil fuels and individual transportation. Consequently, it significantly worsens the air pollution in the area. This study is significant as it allows the government to regulate the air quality in a specific region and it is important to monitor the air pollution in the atmosphere as it has a substantial impact on human health as well as the environment. By conducting this study, it can be seen that there are major positive changes in air quality in Southeast Asia as it is the result of the lockdown and lack of human activities in each country.